2008
DOI: 10.1152/ajpcell.00124.2008
|View full text |Cite
|
Sign up to set email alerts
|

Altered visual function in monocarboxylate transporter 3 (Slc16a8) knockout mice

Abstract: To meet the high-energy demands of photoreceptor cells, the outer retina metabolizes glucose through glycolytic and oxidative pathways, resulting in large-scale production of lactate and CO2. Mct3, a protoncoupled monocarboxylate transporter, is critically positioned to facilitate transport of lactate and H ϩ out of the retina and could therefore play a role in pH and ion homeostasis of the outer retina. Mct3 is preferentially expressed in the basolateral membrane of the retinal pigment epithelium and forms a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 41 publications
(48 reference statements)
8
78
0
Order By: Relevance
“…In support of this hypothesis, previous work from our lab demonstrated that MCT1 and MCT3, the isoforms expressed in RPE in vivo, were not expressed in the RPE of CD147-knockout mice (36). Similar results were observed in MCT3-knockout mice (12). In vitro, we found that silencing MCT4 in the breast cancer cell line, MDA-MB-231, resulted in retention of CD147 in the endoplasmic reticulum (19).…”
Section: Discussionsupporting
confidence: 86%
“…In support of this hypothesis, previous work from our lab demonstrated that MCT1 and MCT3, the isoforms expressed in RPE in vivo, were not expressed in the RPE of CD147-knockout mice (36). Similar results were observed in MCT3-knockout mice (12). In vitro, we found that silencing MCT4 in the breast cancer cell line, MDA-MB-231, resulted in retention of CD147 in the endoplasmic reticulum (19).…”
Section: Discussionsupporting
confidence: 86%
“…Genetic ablation of the basolateral lactate transporter of the RPE, monocarboxylate transporter 3 (Mct3; slc16A8), leads to a strikingly similar ERG impairment as that found in this study, in vivo, and also does not affect responses recorded from isolated rods (79). Loss of Mct3 leads to extracellular accumulation of lactate and probably decreases subretinal pH.…”
Section: Discussionsupporting
confidence: 73%
“…Among these targets, several were noted as important developmental regulators (Meis2) (Conte et al, 2010;Xu et al, 2002) as well as encoding proteins involved in RPE physiology, such as Slc16a8 (Adijanto et al, 2012). Slc16a8 is a member of a family of proton- coupled monocarboxylate transporters that mediate lactate transport across the cell membrane, and Slc16a8 is highly expressed in the RPE, required for visual function and associated with AMD (Daniele et al, 2008;Philp et al, 1998;Priya et al, 2012), and has been experimentally shown to be upregulated by miR-204 (Adijanto et al, 2012). Genes with as yet unknown functions in the RPE, such as Ap1s3, which encodes a subunit of adaptor protein complex, should also be considered when attempting to identify the underlying cause of the phenotype following miRNAs loss from the RPE, as this subunit was recently shown to play a role in the endosomal translocation of signaling components involved in inflammation in skin keratinocytes (Boehm and Bonifacino, 2002;Setta-Kaffetzi et al, 2014).…”
Section: Dicer1 Is Dispensable For Rpe Fate and Survival During Develmentioning
confidence: 99%